A MULTI-LEG LOAD-PLANNING ALGORITHM FOR A HIGH-SPEED FREIGHT TRAIN - Noh, Dong-jin; Kim, Byung-In; Cho, Hyunbo; Park, Jun-Seo (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
This study considers a load-planning problem for a high-speed train called Cargo Transit eXpress (CTX). In the problem, CTX visits a sequence of stations to load and unload unit load devices (ULDs). The train has a given number of wagons with available positions for ULDs, which have respective weights, as well as origin and destination stations. The weight balance among the wagons and within each wagon is crucial for safety because the train moves fast. Furthermore, given that it traverses multiple stations, the weight balance should be maintained among all legs between stations. The problem is how to assign ULDs to specific positions in the wagons considering load balancing at multiple stations. This problem is an NP-hard multi-leg load-planning problem, which has not been studied extensively. An MIP model and a heuristic algorithm are developed to solve the problem. Computational results show the effectiveness of the proposed algorithm.